Secure Image Deduplication Using DICE Protocol for Reducing Storage Cost - Dangre, Ketakee; Pampatwar, Amit; Syeda, Raana (International Journal of Computer Sciences and Engineering, 2025)
Data deduplication is an important aspect for Cloud Storage Providers (CSPs) since it allows them to remove the identical data from their storage successfully. Some techniques have been proposed in the literature for this research area. Among these techniques, the Message Locked Encryption (MLE) scheme is frequently mentioned. Researchers have introduced Message locked Encryption based protocols which provide secured deduplication of data, where the data is in text form. As a result, multimedia data such as images, which are larger in size compared to text files, have not been given much attention. Applying secured data deduplication to such data files could significantly reduce the cost and space required for their storage. This helps in reducing maintenance cost as well for the storage providers. There are several other techniques for Data deduplication. Few of those techniques are as follows SPSD (Secure Perceptual Similarity Deduplication), CSPD (Client Based Secure Provable Deduplication), Image Compression.